Light thinning can improve soil water availability and water holding capacity of plantations in alpine mountains - Gao, Yuan; He, Zhibin; Zhu, Xi; Chen, Longfei; Du, Jun (Frontiers in Plant Science, 2022)
The establishment of large-scale forest plantations in the arid and semi-arid area of the Qilian Mountains in China has effectively protected water and soil resources and enhanced carbon sequestration capacity of forest ecosystems. However, the effects of different management practices in these plantations on soil water holding capacity (SWHC) and soil water availability (SWA) are uncertain in this fragile ecosystem. Here, we investigated the effects of no thinning (NT), light thinning (LT, 20% thinning intensity), and heavy thinning (HT, 40% thinning intensity) on SWHC and SWA at 0-10, 10-20, 20-40, 40-60, and 60-80 cm depths in a forest plantation, and compared them to those in a natural Picea crassifolia forest (NF). Our results revealed that at low soil water suction (0